Mechanisms of ethanol liver damage in rats with different emotionality - O. A. Коstiuk; O. V. Denefil (Kazimierz Wielki University, 2021)
Alcoholic liver disease is associated with liver injury ranging from steatosis to steatohepatitis, fibrosis and cirrhosis. One of the mechanisms of organs damage is cytokines influences. The intensity of injury depends on individual reactivety. The aim of the study was to evaluate changes in the blood of interleukins in the heart of high- and low-emotional (HE, LE) male rats with ethanol hepatosis, hepatitis, fibrosis and cirrhosis of the liver and to determine the degree of liver and heart damage. Material and methods of investigation. The experiments were performed on 72 HE and LE outbred male rats aged 4 months ((control 1, glucose 7 days, acute ethanol hepatitis - EH) and 120 HE and LE autbred male rats aged 5.5-6.5 months (control 2, glucose 67 days, ethanol hepatosis - EHs, ethanol fibrosis - EF, ethanol cirrhosis - EC). The emotionality was determined by "open field" method. Determined in the blood serum Tumor Necrosis Factor Alpha (TNF-α), Interleukin 1 Beta (IL-1β), Interleukin 4 (IL-4), Interleukin 10 (IL-10), alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (AP). All animals underwent histological examination of the liver and heart, right and left ventricles (RV, LV), and ventricular septum (VS) square. Results. In EH increase IL-1β, IL-10 and decrease TNF-α in LE rats. In EHs, EF and EC were decrease of IL-1β, IL-4 and IL-10 in HE rats and decrease of TNF-α, IL-4 and IL-10 in LE rats. In EH decrease ALT (more in LE), AST (more in HE) and increase AP. In HE rats in EHs, EF and EC decreased ALT, in EC increased AST. AP in HE rats increased in EHs; decreased in EF and EC. In LE rats ALT was increased in EHs, and decreased in EC; AST was increased in EC; AP was increased in EHs. In both groups of animals at ethanol damage of a liver remodeling of heart is observed. The earlier and bigger is observed in HE rats. Conclusion. The degree of ethanol damage to the liver and heart depends on the emotionality of the animals and the severity of the simulated pathology, which is more pronounced in highly emotional rats. In the mechanisms of ethanol damage of organism of different emotionality rats take plase cytokines changes. In hepatitis increase IL-1β, IL-10 and decrease TNF-α in low emotions rats. In hepatosis, firosis and cirrhosis were decrease of IL-1β, IL-4 and IL-10 in high emotional rats and decrease of TNF-α, IL-4 and IL-10 in low emotional rats.